Are the supporters of socialism the losers of capitalism? Conformism in East Germany and transition success - Max Deter; Martin Lange (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
The empirical literature is inconclusive about whether a country's democratization has a long-lasting impact on former supporters or opponents of the bygone regime. With newly available individual-level data of former residents of the socialist German Democratic Republic (GDR), we analyze how supporters and opponents of the socialist system performed within the market-based democracy after reunification. Protesters, those who helped to overthrow the socialist regime in the Peaceful Revolution show higher life satisfaction and better labor market outcomes in the new politico-economic system. Former members of the ruling socialist party and employees in state-supervised sectors become substantially less satisfied. These results do not seem to be driven by differential reactions in the post-transition period, but rather by the removal of discriminatory practices in the GDR. Additional results indicate that conformism in the GDR also explains political preferences over the almost three decades after the reunification of Germany.
Keywords: H10; N44; P20; D31; 330; East Germany; state socialism; transition; labor market; life satisfaction